2005
DOI: 10.1210/me.2004-0220
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Proximal Region of the Carboxyl Terminus of the Gonadotropin-Releasing Hormone Receptor (GnRHR) Confers Differential Signal Transduction between Mammalian and Nonmammalian GnRHRs

Abstract: Recently, we demonstrated that the mammalian type-I GnRH receptor (GnRHR) has a high preference for the phospholipase C/protein kinase C (PLC/PKC)-linked signaling pathway, whereas non-mammalian bullfrog (bf) GnRHRs couple to both adenylate cyclase/protein kinase A (AC/PKA)- and PLC/PKC-linked signaling pathways. In the pre-sent study, using AC/PKA-specific reporter (cAMP-responsive element-luciferase) and PLC/PKC-specific reporter (serum-responsive element-luciferase) systems, we attempted to identify the mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 51 publications
0
37
1
1
Order By: Relevance
“…The reactions were terminated by replacing medium with ice-cold 5% trichloroacetic acid containing 1 mM ATP and 1 mM cAMP. [ 3 H]cAMP and [ 3 H]ATP were separated on an AG50W-X4 resin (Bio-Rad, USA) and alumina columns as previously described (Oh et al, 2005). The cAMP accumulation was expressed as…”
Section: Methodsmentioning
confidence: 99%
“…The reactions were terminated by replacing medium with ice-cold 5% trichloroacetic acid containing 1 mM ATP and 1 mM cAMP. [ 3 H]cAMP and [ 3 H]ATP were separated on an AG50W-X4 resin (Bio-Rad, USA) and alumina columns as previously described (Oh et al, 2005). The cAMP accumulation was expressed as…”
Section: Methodsmentioning
confidence: 99%
“…Pituitary GnRH receptors are thought to primarily signal through G q/11 , resulting in the stimulation of the IP 3 second messenger system; however, G s activation and cAMP signaling has been reported as well , Grosse et al 2000, Liu et al 2002, Oh et al 2005. G-protein coupling to type I GnRH receptors clearly occurs within the intracellular loops (ILs), where several motifs have been identified that may be involved in G-protein coupling (see Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…GnRH receptor signaling has been characterized in several systems, and is primarily thought to function through the Inositol 1,4,5-triphospate (IP 3 ) second messenger pathway; however, type II GnRH receptors and in some cases type I GnRH receptors have been shown to also activate cAMP signaling , Grosse et al 2000, Liu et al 2002, Oh et al 2005. The presence or absence of the C-terminal tail in type II and type I GnRH receptors respectively could possibly explain the signaling disparity between the two groups, where, for example, histidinephenylalanine-arginine-lysine (an HFRK) motif in the membrane proximal region of bullfrog type II GnRH receptors was recently shown to be required for cAMP signaling (Oh et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GnRH-R2 GnRH-R3 2 3 5 GnRH-R GnRH-R1 GnRH-R 53,54 GnRH-R2 GnRH-R3 C 47,55 IP3 cAMP 55,56 GnRH-R2 GnRH-R3 …”
Section: Gnrh-runclassified